Anti‐nucleosome autoantibodies as markers for autoimmune hepatitis and their correlation with disease activity. Issue 4 (7th May 2013) - Yokokawa, Junko; Kanno, Yukiko; Abe, Kazumichi; Saito, Hironobu; Monoe, Kyoko; Katsushima, Fumiko; Sakamoto, Natsumi; Takahashi, Atsushi; Yokokawa, Hirohide; Ohira, Hiromasa
<x xml:space="preserve">Abstract</x> Aim To assess the prevalence of autoantibodies against nucleosomes (anti‐nucleosome Ab) in patients with autoimmune hepatitis (AIH), examine the correlation between anti‐nucleosome Ab and disease activity, and evaluate the effectiveness of anti‐nucleosome Ab in predicting relapse. Methods We analyzed serum anti‐nucleosome Ab levels in 38 patients with AIH by enzyme‐linked immunosorbent assay, and assessed their correlation with clinical characteristics. Results Anti‐nucleosome Ab levels were significantly higher in AIH, but not in patients with chronic hepatitis B (n = 20) or chronic hepatitis C (n = 20), compared to healthy controls (n = 15). The positive prevalence of anti‐nucleosome Ab was 71.1% in AIH. Anti‐nucleosome Ab levels were significantly lower during remission compared to that during flares within the same patients with AIH. Total bilirubin levels were significantly higher in patients with anti‐nucleosome Ab levels of 53.7 U/mL or more compared to those with less than 53.7 U/mL at disease onset. Analysis of the reduction in anti‐nucleosome Ab by immunosuppressive therapy in 16 AIH patients revealed that age at disease onset was significantly lower and IgG levels and relapse rates were significantly higher in patients with a reduction rate of less than 35% compared to those with a reduction rate 35% or more. The International Autoimmune Hepatitis Group score and γ‐globulin levels were also higher in patients with reduction rates of less than 35% (borderline significance). Conclusion Anti‐nucleosome Ab in AIH patients may be useful markers not only for disease diagnosis, but also for activity assessment and relapse prediction.